"Heritage-for-Peace and Development": An Opportunity Not to be Missed - Milenković, Miloš (Etnoantropolos̆ki problemi, 2021)
The dominant approach of the international community to the subject of our research and teaching is to instrumentalise cultural heritage safeguarding within stabilisation and development programs in post-conflict regions. Since the turn of the Millennium, cultural heritage safeguarding has been among the crucial instruments used by the international community, especially in post-conflict regions, for: reconciliation and peace building; development of a common sense of belonging; promoting mutually respectful dialogue in culturally complex societies. Many international organizations, such as the UN, the OSCE High Commissioner on National Minorities, NATO, the Stability Pact for South Eastern Europe, the World Bank, the United Nations Development Program, the Council of Europe, and the EU, promote the management of ethno-political conflicts as their priority. Their agendas follow the principles of a) the overall relevance of cultural heritage for society and b) the importance of social networks for peace-building and peacekeeping in post-traumatic contexts. Instead of opposing this peace and development oriented paradigm from either anti-realist or nationalist perspective, we can recognize it, apply it and use it to improve the social status of social sciences and humanities in Serbia. Anthropological and critical heritage studies-based criticism of UNESCO-driven, state-governed ICH safeguarding fails to comprehend that standard academic constructivist analyses of a community’s key symbols of identity are offensive from the native’s point of view. Our typical analyses unwittingly confuse, annoy or even insult a great majority of the wider public who view/perceive collective identity as something given, inherited and real analogously to the objects and processes of the physical world. Consequently, our theoretical work counterindicates both peacekeeping, stability-building efforts by the international community in post-conflict regions and the goals of critical social science (which it nominally represents). Hence, a novel approach is required, one prioritising heritage stakeholder inclusion (and not our theoretical or ethnoreligious commitments). It is precisely the studies of nationalism and its consequences which forbid us to think of heritage as something useful, a counter-intuitive method for achieving fundamental anthropological goals. As communities regularly perceive their identities as objective and real, and see a critical social theory approach to their customs and traditions as confusing, non-academic, illegitimate or even offensive, I here propose a shift from constructionist criticism, standard in anthropology, to realist instrumentalism, typical of ethnology, in order to boost ICH safeguarding potential for achievement of both social and disciplinary-specific goals.